ANALISIS POTENSI EKONOMI DESA DAN PROSPEK PENGEMBANGANNYA MELALUI SISTEM INFORMASI PEMETAAN POTENSI DESA (SIPENA) - Jantianus, Jantianus; Khairul; Indahwati, Rini; Tambun, Rosmaida; Naibaho, Dameria (Jurnal Budgeting, 2025)
In improving the economy of rural communities, it is necessary to map the available economic potential. Primary data collection on the economic potential of the village, namely in Nangbelawan, is carried out by interviewing partners, directly reviewing the available potential. From all the data and information collected in the integration in a website system: pesikap-nangbelawan.com. Information needed by users about the economic potential of the village can be obtained, including, agriculture, animal husbandry, fisheries, tourism, and liquid organic fertilizer. Natural resources that are quite fertile, sufficient rainfall, easy marketing of agricultural products, potential sources of labor are the strengths of the Nangbelawan village, but human resources are still very weak in utilizing the available potential. The economic potential that is the mainstay in the Nangbelawan village is carrot farming and cattle farming. The potential for livestock farming is very supportive because carrot agricultural waste can be used for cattle feed. By mapping the economic potential of the village through the pesikap-nangbelawan.com website, the development of the village economy that can be developed can be explored. In the future, this research will be developed so that the pesikap-nangbelawan.com website can be used as a patron for every village in North Sumatra in exploring and developing the economic potential of each village. Keywords: mapping, potential, information, development